Factors responsible for trade union membership in Mbeya city council, Tanzania - Merydon, Godian (Mzumbe University, 2024)
A dissertation submitted to the School of Public Administration and Management (SOPAM) for the partial fulfillment of the requirements for award of the Master of Science in Human Resource Management (MSc.HRM) of Mzumbe University